The effect of hearing loss on neural processing - Jonathan E Peelle (Frontiers Research Topics, 2015)
Efficient auditory processing requires the rapid integration of transient sensory inputs. This is exemplified in human speech perception, in which long stretches of a complex acoustic signal are typically processed accurately and essentially in real-time. Spoken language thus presents listeners' auditory systems with a considerable challenge even when acoustic input is clear. However, auditory processing ability is frequently compromised due to congenital or acquired hearing loss, or altered through background noise or assistive devices such as cochlear implants. How does loss of sensory fidelity impact neural processing, efficiency, and health? How does this ultimately influence behavior? This Research Topic explores the neural consequences of hearing loss, including basic processing carried out in the auditory periphery, computations in subcortical nuclei and primary auditory cortex, and higher-level cognitive processes such as those involved in human speech perception. By pulling together data from a variety of disciplines and perspectives, we gain a more complete picture of the acute and chronic consequences of hearing loss for neural functioning.